Analysis of contraceptives supply in Peru - Távara Orosco, Luis (2015)
Objectives. To perform bibliography search on contraception, to analyze contraceptive methods range offered by both the Ministry of Health (MINSA) and the private sector, to verify contraceptives available in the market, to examine double protection and to recommend what new methods should be included in the offer. Methods. Review of the scientific literature, analysis of ENDES and MINSA reports, review of contraceptives list in the market, advantages and users’ satisfaction with new methods, interview with MINSA officials and professionals that deliver contraceptives in the private sector and systematization of findings. Findings. There is a diversity of contraceptive methods. Family planning improves women and children’s health and survival, contributes to environment support and reduction of poverty. Contraceptives are varied and effectiveness is also varied. Variety contributes to more method use and more satisfaction of users. Provision of contraceptives should develop information activities oriented to users to adopt conducts of double protection that represents an excellent intervention to reduce STI/HIV frequency and unwished pregnancies. ENDES report fecundity global rate has not decreased notwithstanding women’s wishes to have fewer children, adolescents’ fecundity specific rate has a tendency to increase and contraceptive use, even increasing in the past years, has been at the expense of periodic abstinence. Discontinuation rate during the first year of use e 50% in women in fertile age. Main contraceptives provider is the Ministry of Health that has a reduced mixture of products, more diverse in the private sector. Conclusions. In Peru, fecundity rate has not changed substantially and this is greatly due to deficiencies of the family planning program that does not satisfy offer and presents a reduced mixture of contraceptives.